Attitudes towards marriage among some urban Chinese singles / Thong Kooi Lin - Thong , Kooi Lin (1988)
The main them of this study on marriage postponement among Chinese singles in Kuala Lumpur. Discussion is focused on the attitudes towards marriage and other related issues, socio economic backgrounds and lifestyles of the target group. Besides determining the factors that encourage late marriage, some sex differences in attitudes are also examined. Chapter I gives a brief review on literature related to the research problem, research objectives, scope, methodology, problems and limitations. Chapter II deals with the Chinese marriage institution according to the customary and statutory laws, the trend towards late marriage and factors affecing it. Chapter III gives a description of the respondents’ personal background, family backgrounds, social mixing and corting experiances. Chapter IV discusses the respondents' conception of marriage, functions of marriage and attitudes towards trial marriages, polygyny, mixed marriages and inter-faith marriages. It also deals with some important criteria in mate-selection such as personality, physical appearance, age, education and income. Chapter V deal with isssues on singlehood. It examines the reasons for remaining single, sex discrimintion, life problems faced by singles and permanent singlehood. Chapter 6 concludes the findings of this research by giving the main factors that encourge the target group to delay marriage, sec differeces in attitudes and results from the tests.